ETHNOMARKETING - A NEW PARADIGM THAT REFLECTS MARKETING’S CONCERN FOR THE CULTURAL DIMENSION OF THE MARKET - MIRELA-CRISTINA VOICU; ALINA-MIHAELA BABONEA; OTILIA-ELENA PLATON (Challenges of the Knowledge Society)
Culture has often been regarded as one of the main determinants of consumer behavior and of the symbolism acquired by certain products. It is well known that states are composed of many subcultures and that cultural diversity is an ever-present topic. Culture has invaded the entire current range of business, its presence is seen everywhere, and marketing makes no exception. In this context and considering culture as an important factor that conducts and guides the entrepreneurial success, the following paper reveals some important concepts, characteristics and principles of ethnomarketing for a better exploitation of market opportunities, especially on its consumer behavior dimension.